Insight into the precuneus: a novel seizure semiology in a child with epilepsy arising from the right posterior precuneus. Issue 3 (1st October 2015) - Mailo, Janette; Tang‐Wai, Richard
Abstract To date, there is limited understanding of the role of the precuneus. fMRI studies have suggested its involvement in a wide spectrum of highly integrated tasks, including spatially‐guided behaviour, visuo‐spatial imagery, and consciousness. We present a patient with intractable parietal lobe epilepsy arising from a lesion localized to the right precuneus. Two seizure types with distinct semiologies were captured on video‐EEG monitoring. The first type consisted of an urge described as a "feeling of wanting to move". On video analysis, the patient is seen to turn his head and body to his left. He remains conscious, he is able to answer questions and when asked, he can look to his right. This seizure was associated with an ictal pattern localized to the right parieto‐occipital region. The second seizure type consisted of reading‐induced visual distortion with macropsia and micropsia. Interictally, intermittent rhythmic slowing and spikes were seen and localized to the parietal midline and the right parieto‐occipital regions. Our patient's seizures are positive phenomena of the right precuneus and its related processing network. They represent unique seizure semiologies that offer further insight into the role of the precuneus in spatial awareness, visuo‐spatial processing and consciousness.